Spirituality and faith in the treatment of oncologic patients: integrative review (Research, Society and Development, 2022)
Spirituality influences human behavior and is related to the search for meaning. It is considered a fundamental component to overcome adversity and frustration. The attachment to spirituality positively influences the biopsychosocial health of cancer patients. The objective was to identify spirituality and faith in the face of treatment in cancer patients. This is an integrative literature review, in the databases: SciELO, LILACS, BDENF and MEDLINE, using Boolean operators in conjunction with the descriptors of health (DeSC) in the following combinations: "Spirituality" AND "Palliative care" AND "Oncology" AND " Psychological adaptation", in English and Portuguese languages, which sought articles published between 2017 and 2021. The final sample consisted of 14 articles. The results point to the importance of spirituality and faith in quality of life and well-being, serve as support, resignification, and expectations of healing. Both are strategies to face the oncologic diagnosis, as a search for answers about life, strengthen the patients when facing the impacts of the disease, and stimulate their lives to face the procedures. Furthermore, they establish a positive method for relieving insecurities in the face of stigma, and personal issues pertinent to the circumstances of the disease. Furthermore, they contribute to the acceptance of cancer, besides the significant improvement in the prognosis.